ANALISIS PENGARUH KUALITAS PELAYANAN DAN KENYAMANAN KONSUMEN TERHADAP KEPUASAN KONSUMEN (STUDI KASUS MAHASISWA POLITEKNIK CENDANA ANGKATAN 2020) - Locarso, Charyns; Yuliana, Yuliana; Sutarno, Sutarno (Jurnal KAFEBIS, 2024)
In this research, the author wants to identify the problem of “Is there an influence of service quality and consumer comfort on consumer satisfaction (Case Study of Cendana Polytechnic Students Class of 2020)?”. The aim is to determine the influence of service quality and consumer comfort on consumer satisfaction (Case Study of Cendana Polytechnic Students Class of 2020), Medan. The author uses associative quantitative research methods. Consumer conveinience is a comprehensive assessment of the feelings of safety and comfort felt by people who use products or services provided by the company. Consumer satisfaction is a comprehensive assessment given by consumers regarding the level of satisfaction they feel after using the products or services provided by the company.From the research results it can be concluded that service quality and consumer conveinience influence consumer satisfaction.